Fuel: An Ecocritical History Fuel: An Ecocritical History - Heidi C. M. Scott (Environmental Cultures, 2018)
The first history of changing attitudes to fuel - from biomass to fossil fuels and renewable energy - in the literature and culture of the last 250 years.